2018
DOI: 10.1007/s12519-018-0167-1
|View full text |Cite
|
Sign up to set email alerts
|

Determinants for asthma control, quality of life and use of complementary and alternative medicine in asthmatic pediatric patients in four cities

Abstract: There are some clinical and cultural differences among the four southern Chinese cities within the Guangdong province. This study identifies potentially modifiable environmental and treatment factors associated with poor asthma control and QoL for health-care interventions. Having a smoker in the family is independently associated with poor asthma control and QoL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…Some studies have confirmed the positive effects of yoga on children's health (13,14). Yoga/pranayama breathing exercises are among the nonpharmacological methods that play a special role in the treatment of asthma (15,16), and they are currently a preferred alternative treatment for asthma globally (17). Yoga helps reduce bronchospasm and breathlessness by modifying the breathing pattern, reducing hyperventilation, and normalizing CO 2 levels (18).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have confirmed the positive effects of yoga on children's health (13,14). Yoga/pranayama breathing exercises are among the nonpharmacological methods that play a special role in the treatment of asthma (15,16), and they are currently a preferred alternative treatment for asthma globally (17). Yoga helps reduce bronchospasm and breathlessness by modifying the breathing pattern, reducing hyperventilation, and normalizing CO 2 levels (18).…”
Section: Introductionmentioning
confidence: 99%
“…In the presence of asthma, treatment of AR is often overlooked, and poor control of AR has been shown to be one of the causes of refractory and recurrent asthma [ 6 8 ]. Control of AR reduces the incidence of asthma attacks and associated hospitalizations [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…21 Lower socioeconomic status of the family and exposure to household moulds contributed to lower QoL. 21 Another study 22 reported better asthma control was associated with better Pediatric Allergic Disease QoL Questionnaire (PADQLQ).…”
Section: Introductionmentioning
confidence: 99%